IDENTITAS GURU PAI ABAD 21 YANG IDEAL PADA PEMBELAJARAN FIQH DI SEKOLAH DAN MADRASAH - Firman Mansir (IAIN Ponorogo, 2020)
AbstractThis research explains that in 21st century, education is faces by some quite complex challenges. In this 21st century, advances in science and technology in all fields are increasingly narrowing the world. Compared to the previous century, in this century, professional teachers must have a wider range of competences. Teacher in 21st century must be able to improve personal skills, technical skills, social skills and pedagogical skills. Islamic Education teachers in 21st century are also expected to develop positive relationships with students and the school community using technology as a tool to raise teaching standards. Especially in learning Islamic religious education, in fiqh, an ideal or professional teacher is needed to form the skills of a teacher in building the enthusiasm of students in science, religion and technology. The ideal PAI teacher has the ability to develop and combine various learning strategies and methods to spur students' enthusiasm for learning because students nowadays know information very easily. AbstrakPenelitian ini menjelaskan bahwa pada abad 21 ini pendidikan dihadapkan dengan berbagai tantangan yang cukup kompleks. Pada abad 21 ini, kemajuan ilmu pengetahuan dan teknologi di semua bidang semakin mempersempit dunia. Dibandingkan dengan abad yang sebelumnya, pada abad ini guru yang profesional harus mempunyai kompetensi yang lebih luas. Guru abad 21 ini harus mampu meningkatkan keterampilan pribadi, keterampilan teknis, keterampilan sosial dan keterampilan pedagogik. Guru PAI abad 21 juga diharapkan dapat mengembangkan hubungan positif dengan peserta didik dan komunitas sekolah, menggunakan teknologi sebagai alat untuk meningkatkan standar pengajaran. Terutama dalam pembelajaran pendidikan agama Islam, dalam fiqih guru yang ideal atau profesional sangat dibutuhkan untuk membentuk kecakapan seorang guru dalam membangun semangat peserta didik dalam hal sains, ilmu agama dan teknologi. Guru PAI yang ideal memiliki kemampuan untuk mengembangakan dan memadukan berbagai strategi dan metode belajar untuk memacu semangat belajar peserta didik, karena pada zaman saat ini peserta didik mengetahui infomasi-informasi dengan sangat mudah.